Wordwall sebagai Media Pembelajaran Kosakata Bahasa Indonesia bagi Peserta Didik Autis - Rusmiyanti Rusmiyanti; Hermanto Hermanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The objective of this study is to develop a Wordwall-based learning media that is feasible, practical, and efficient for improving Indonesian vocabulary among third-grade students with autism. The research uses the Research and Development (R&D) type using the ADDIE model which includes 5 stages, namely Analyze, design, development, implementation and Evaluation. Field trials at SLB Negeri 1 Bantul and SLB PGRI Sumbersari with eleven students as research subjects. The feasibility of the media product is obtained from the assessment of media and material experts. The practicality of the media is obtained from the teacher response test. The research instruments used interviews, observations, questionnaires, and performance assessments. Data analysis used qualitative and quantitative techniques. The results of the Wordwall media research were declared feasible and practical, the results of the material validation score were 4.23 with the category "feasible", the media validation score was 4.34 with the category "feasible", and the teacher assessment score was 5.0 with the category "practical". The media was declared effective in increasing students' vocabulary with a significance of 0.05. increased from pretest 59.09 to posttest 81.81.